GAMBARAN SANITASI TEMPAT BERDAGANG WARUNG PENYET DI KECAMATAN TEMBALANG - Barkah Haryo Wasisto; Martini Martini; Sri Yuliawati; Susiana Purwantisari (Jurnal Kesehatan Masyarakat (Undip), 2017)
District Tembalang is one of the sub-district in the city of Semarang with many colleges so that there are many penyet restaurant. The purpose of this study was to determine the factors that influence the contamination of Salmonella sp on a vegetables penyet in District Tembalang, Semarang City. This study is observational analytical survey method using cross sectional design. These samples included 40 penyet restaurant observed water and vegetables fresh vegetables supplied to consumers. Data were analyzed by frequency distribution and bivariate with chi square test. The results showed the storage of vegetables vegetables using plastic bags (50%); the basket (27.5%) and sacks (22.5%). Sanitation trade places category is good (57.5%). There is a statistically significant relationship between sanitation trade places (p = 0.006) with Salmonella sp contamination in fresh vegetables. Traders are paying less attention sanitation and personal hygiene as well as a sanitation vegetables can contaminate vegetables in the vegetable vegetables Salmonella sp. Penyet restaurant traders should begin to attention about hygiene and sanitation where trade, personal hygiene when to trade, and improve the way the vegetable washing vegetables to reduce the risk of contamination of Salmonella sp.